Atypical presentation of scrub typhus encephalitis with cerebral hemorrhage - Mukhopadhyay, Arka; Bandyopadhyay, Dipanjan; Chakrabarti, Debasis; Bhadra, Anamika (International Journal of Research in Medical Sciences, 2022)
Scrub typhus, an arthropod borne infection caused by the rickettsial organism Orientia tsutsugamushi, is a fairly common disease in north-eastern sub-Himalayan India, particularly the forest areas, and is known to manifest with varied presentations ranging from non-specific fever to severe multi-organ complications. Hemorrhagic manifestations described in the literature are mostly gastrointestinal and genitourinary, secondary to vasculitis and/or thrombocytopenia, but reports of cerebral hemorrhage have been extremely rare. We report a case from sub-Himalayan eastern India where a 23 years old male tea plantation worker presented with recurrent convulsions with magnetic resonance imaging (MRI) brain showing multiple parenchymal hemorrhages with encephalitis involving both the cerebral hemispheres. Although patient developed fever and acute kidney injury later in the course, these were not the presenting complaints despite fever being the most consistent sign of a scrub typhus infection. We suggest consideration of scrub typhus as a differential diagnosis of a cerebral hemorrhage in endemic regions.